2021
DOI: 10.1073/pnas.2015215118
|View full text |Cite
|
Sign up to set email alerts
|

Reassessment of the phylogenetic relationships of the late Miocene apes Hispanopithecus and Rudapithecus based on vestibular morphology

Abstract: Late Miocene great apes are key to reconstructing the ancestral morphotype from which earliest hominins evolved. Despite consensus that the late Miocene dryopith great apes Hispanopithecus laietanus (Spain) and Rudapithecus hungaricus (Hungary) are closely related (Hominidae), ongoing debate on their phylogenetic relationships with extant apes (stem hominids, hominines, or pongines) complicates our understanding of great ape and human evolution. To clarify this question, we rely on the morphology of the inner … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 77 publications
(87 reference statements)
0
11
0
Order By: Relevance
“…The bony labyrinth morphology has been proven to be a very efficient marker for the reconstruction of mammal phylogeny (e.g., Mennecart et al 2016Mennecart et al , 2017Urciuoli et al, 2021). Though based on only two geographically close wild boar populations and a limited number of domestic pigs (especially for the intensively bred category), extant wild boar and domestic pigs differ in their semicircular canal size and shape.…”
Section: Discussionmentioning
confidence: 99%
“…The bony labyrinth morphology has been proven to be a very efficient marker for the reconstruction of mammal phylogeny (e.g., Mennecart et al 2016Mennecart et al , 2017Urciuoli et al, 2021). Though based on only two geographically close wild boar populations and a limited number of domestic pigs (especially for the intensively bred category), extant wild boar and domestic pigs differ in their semicircular canal size and shape.…”
Section: Discussionmentioning
confidence: 99%
“…We compared StW 578 to extant specimens and Sts 5 by using landmarkfree registration based on smooth and invertible surface deformation. [26][27][28][29][30] This approach has been previously applied to a number of craniodental and postcranial structures, including endocasts 27,29 , enamel-dentine junctions 28,31 , vertebrae 32 and bony labyrinths 33 and comparisons between the landmark-based and landmark-free approaches have revealed the ability of the latter approach for capturing geometric details and for statistical determination of geometric correspondence 34 . Because the StW 578 calotte is partial, instead of using the whole surface to align specimens as in previous studies [27][28][29] , we used four landmarks, i.e.…”
Section: Shape Analysismentioning
confidence: 99%
“…In a situation equivalent to that seen in cercopithecoids (see "Crown Cercopithecidae"), the early Miocene African fossil record of Hominoidea is characterized by a diversity of stem taxa (proconsuline and nyanzapithecine "proconsulids") without any evidence of crown representatives (Harrison, 2010b;Stevens et al, 2013;Nengo et al, 2017;Almécija et al, 2021).…”
Section: Calibrating Taxon Kenyapithecus Wickerimentioning
confidence: 99%
“…A number of "dryopiths" (sensu Almécija et al, 2021;Urciuoli et al, 2021) from Europe, including the ~9.6-8.7 Ma old Ouranopithecus macedoniensis (Sen et al, 2000;Koufos et al, 2016), have been found to be stem hominines in some published phylogenetic analyses (e.g., Begun et al, 2012), but not others (e.g., Alba et al, 2015, and their position appears sensitive to analytical assumptions (Young and MacLatchy, 2004;Worthington, 2012). Given the ongoing controversy regarding the affinities of the European "dryopiths" (see Benoit and Thackeray, 2017;Fuss et al, 2018;Almécija et al, 2021), we follow Gilbert et al (2020) in viewing them as Hominoidea incertae sedis, and do not use them as the oldest record of Homininae. Instead, we use the slightly younger Chororapithecus abyssinicus, which we recognize as a crown hominine (stem gorillin), with an age range of 8.33-7.5 Ma (see "Crown Homininae" below).…”
Section: Calibrating Taxon Sivapithecus Indicusmentioning
confidence: 99%